“Análisis del impacto económico derivado de la covid-19 y las estrategias de reactivación de las pymes comerciales del cantón Valencia”. - Reyes Cedeño, Mayra Katherine (2022)
Small and medium-sized commercial companies are of great importance in the economic field, where the research was carried out with the aim of establishing the analysis of the economic impact derived from covid-19 and the reactivation strategies carried out by commercial SMEs in the Valencia canton. It was determined that small and medium-sized companies are the main economic engine, since they are in charge of satisfying the needs of society, therefore, with the economic reactivation, the direct beneficiaries were the owners and collaborators of the commercial establishments and the beneficiaries indirect were the customers who bought their products to satisfy their needs. The methodology for the execution of the project was field and bibliographical research. The research methods were the theoretical method where we determined the background of the research, the analytical method that served to develop the analysis of the results obtained, and the inductive method applied in the identification of the study population.For data collection, we applied the survey technique to 277 owners of SMEs, to whom the questionnaire was applied in order to obtain the real results in the face of the economic situation, which was validated by the Cronbach's Alpha statistic in the that the pilot test was carried out with 15 items, giving us a value equivalent to 0.837 of reliability in the SPSS system. The study population is made up of 903 SMEs from the commercial sector registered in the Municipal GAD of the Valencia canton, with these data the sampling was established considering the 5% error and a confidence level of 95%, in order to identify how many SMEs to survey. The results achieved were the knowledge obtained about the economic impact and the most used strategies that some businesses applied during and after the pandemic